2005
DOI: 10.1111/j.1365-2672.2004.02467.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Staphylococcus aureus enterotoxin types within single samples of raw milk and raw milk products

Abstract: Aim: To find out if testing of up to 10 Staphylococcus aureus isolates from each sample from raw milk and raw milk products for staphylococcal enterotoxin (SE) might increase the chances of identifying potential sources of food intoxication. Methods and Results: Altogether 386 S. aureus isolates were tested for the presence of SE by reversed passive latex agglutination (SET-RPLA), and SE genes (se) by a multiplex polymerase chain reaction (PCR). In 18 of 34 (53%) S. aureus positive samples a mixture of SE and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 25 publications
6
39
2
4
Order By: Relevance
“…This has also been reported as the most frequent gene in staphylococcus from goat milk by Scherrer et al (2004) and Lyra et al (2013), who observed secin 42% and 55.6% of positive staphylococci, respectively. The gene sec was also reported by Loncarevic et al (2005) as the most frequent classical enterotoxin-encoding gene amongst Staphylococcus from goat milk. The presence of this gene was seen in 71% (Mork et al 2010) and 86% (Silva et al 2005) of Staphylococcus recovered from healthy goats and goats with udder infections, respectively.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…This has also been reported as the most frequent gene in staphylococcus from goat milk by Scherrer et al (2004) and Lyra et al (2013), who observed secin 42% and 55.6% of positive staphylococci, respectively. The gene sec was also reported by Loncarevic et al (2005) as the most frequent classical enterotoxin-encoding gene amongst Staphylococcus from goat milk. The presence of this gene was seen in 71% (Mork et al 2010) and 86% (Silva et al 2005) of Staphylococcus recovered from healthy goats and goats with udder infections, respectively.…”
Section: Resultsmentioning
confidence: 84%
“…Conversely, a higher frequency of novel enterotoxin-encoding genes compared to the classic ones has been reported worldwide (Scherrer et al 2004, Loncarevic et al 2005, Rall et al 2008. In a different study performed in Paraiba, the novel genes seb, sed, see and seh were not detected in staphylococci from bulk goat milk (Lyra et al 2013).…”
Section: Resultsmentioning
confidence: 97%
“…It seems, also on the basis of the present results, that PCR is able to identify a higher number of potentially enterotoxin producing strains than immunological tests. These findings may be explained by the fact that se gene detection does not necessarily indicate the production of toxins and their biological activity (17). The presence of enterotoxigenic S. aureus in raw milk poses a potential health risk to consumers.…”
Section: Discussionmentioning
confidence: 95%
“…Kalorey Ak-Amikacin, Caz-ceftazidime, G-gentamicin, K-kanamycin, Net-netilmicin, Ox-oxacillin, P-penicillin, Tob-tobramycin. (20). Thus, the design and implementation of region-specific surveillance programs on the molecular epidemiology and resistance pattern of S. aureus associated with bovine mastitis is essential in India.…”
Section: Discussionmentioning
confidence: 99%